Inhibition of inflammatory liver injury by the HMGB1-A box through HMGB1/TLR-4/NF-κB signaling in an acute liver failure mouse model - Luo, Lidan; Wang, Shuai; Chen, Bohao; Zhong, Mei; Du, Ruili; Wei, ChunShan; Huang, Furong; Kou, Xinhui; Xing, Yufeng; Tong, Guangdong (Frontiers in Pharmacology, 2022)
We aimed to investigate the preventive effect of high mobility group box 1 (HMGB1)-A box and the mechanism by which it alleviates inflammatory injury in acute liver failure (ALF) by inhibiting the extracellular release of HMGB1. BALB/c mice were intraperitoneally (i.p.) administered LPS/D-GalN to establish an ALF mouse model. HMGB1-A box was administered (i.p.) 1 h before establishing the ALF mouse model. The levels of extracellularly released HMGB1, TLR-4/NF-κB signaling molecules, the proinflammatory cytokines TNF-α, IL-1β and IL-6 and COX-2 were measured in the liver tissue and/or serum by Immunohistochemistry, Western blotting and Enzyme-linked immunosorbent assay (ELISA). The levels of extracellularly released HMGB1, TLR-4/NF-κB signaling molecules and proinflammatory cytokines were measured in Huh7 cells as well as LPS- and/or HMGB1-A box treatment by confocal microscopy, Western blotting and ELISA. In the ALF mouse model, the levels of HMGB1 were significantly increased both in the liver and serum, TLR-4/NF-κB signaling molecules and proinflammatory cytokines also was upregulated. Notably, HMGB1-A box could reverse these changes. HMGB1-A box could also cause these changes in LPS-induced Huh7 cells. HMGB1-A box played a protective role by inhibiting inflammatory liver injury via the regulation of HMGB1/TLR-4/NF-κB signaling in the LPS/D-GaIN-induced ALF mouse model, which may be related to inhibiting the extracellular release of HMGB1.